Monetary policy analysis with potentially misspecified models - Marco Del Negro; Frank Schorfheide (European Central Bank (ECB), 2005)
This paper proposes a novel method for conducting policy analysis with potentially misspecified dynamic stochastic general equilibrium (DSGE) models and applies it to a New Keynesian DSGE model along the lines of Christiano, Eichenbaum, and Evans (JPE 2005 and Smets and Wouters (JEEA 2003). Specifically, we are studying the effects of coefficient changes in interest-rate feedback rules on the volatility of output growth, inflation, and nominal rates. The paper illustrates the sensitivity of the results to assumptions on the policy invariance of model misspecifications.
Keywords: C32; 330; Bayesian Analysis; DSGE Models; Model Misspecification; Geldpolitik; Unvollkommene Information; Allgemeines Gleichgewicht; VAR-Modell; Modellierung; Schätzung